Servant leadership on the inter-church deliberation institute of Surabaya - HARTONO, HENOCH WILIANTO; SUYANTO, BAGONG; ADAM, SUBAGYO (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT Poverty reduction consists of various elements, one important element of society in poverty alleviation was faith based organizations such as the Inter-Church Deliberation Institute of Surabaya (BAMAG). The purpose of this study was to analyzed the activities and practices of servant leadership in BAMAG. The design of this study used a qualitative approach. The results explained that transformative and innovative servant leadership has not just to maintained and remained loyal to the social conscience and the organization of the BAMAG but also to developed together with its members the best service to the social community to reduce poverty. RESUMEN La reducción de la pobreza consta de varios elementos, un elemento importante de la sociedad en el alivio de la pobreza es la organización basada en la fe, como el Instituto de Deliberación Intereclesial de Surabaya (BAMAG). El propósito de este estudio fue analizar las actividades y prácticas del liderazgo de servicio en BAMAG. El diseño utilizó un enfoque cualitativo. Los resultados explicaron que el liderazgo de servicio transformador e innovador no solo tenía que mantener y permanecer leal a la conciencia social y a la organización de BAMAG, sino que también se desarrolló junto con sus miembros que habían prestado el mejor servicio a la comunidad social para reducir la pobreza.